2019
DOI: 10.3390/jcm8091336
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cardiac Arrest and Respiratory Failure Using Feasible Artificial Intelligence with Simple Trajectories of Patient Data

Abstract: We introduce a Feasible Artificial Intelligence with Simple Trajectories for Predicting Adverse Catastrophic Events (FAST-PACE) solution for preparing immediate intervention in emergency situations. FAST-PACE utilizes a concise set of collected features to construct an artificial intelligence model that predicts the onset of cardiac arrest or acute respiratory failure from 1 h to 6 h prior to its occurrence. Data from the trajectory of 29,181 patients in intensive care units of two hospitals includes periodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 30 publications
2
81
0
3
Order By: Relevance
“…Previously, Jeongmin et al 23 introduced feasible artificial intelligence with simple trajectories to predict adverse catastrophic events (FAST‐PACE), which consisted of simple vital signs, and found that FAST‐PACE outperformed MEWS and NEWS. In another study, Churpek and colleagues 13 developed nine common machine learning models for ward deterioration in five hospitals, and showed that all models were more accurate than MEWS.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Jeongmin et al 23 introduced feasible artificial intelligence with simple trajectories to predict adverse catastrophic events (FAST‐PACE), which consisted of simple vital signs, and found that FAST‐PACE outperformed MEWS and NEWS. In another study, Churpek and colleagues 13 developed nine common machine learning models for ward deterioration in five hospitals, and showed that all models were more accurate than MEWS.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of studies have used artificial intelligence, including machine learning, to estimate clinical scores and assess patients or provide warnings regarding adverse events [ 37 - 40 ]. In those studies, a series of various techniques were used according to the scale of scores, the capacity of collected data, and the skewness of data.…”
Section: Discussionmentioning
confidence: 99%
“…AI technology develops and improves the method of learning. It performed measurement more consistently and faster than human without any interruption [111] , [112] , [113] , [114] . It quickly scans the patient's report to update/remind the patient for an appointment and positively impact human life.…”
Section: Artificial Intelligence Applications In Cardiology During Comentioning
confidence: 99%